Transplantation Imaging (Springer International Publishing, 2018)
This book describes the multimodality imaging of cardiac, lung, liver, kidney, pancreas, and small bowel transplants in donors and recipients. The volume of transplantation of solid organs has increased substantially and has become common practice in medicine. Radiological evaluation of transplanted organs such as the heart, lungs, liver, pancreas, and kidneys is critical, both in potential donors (as is the case in liver and kidney transplantation) and in preoperative and postoperative evaluations of recipients. Understanding the often complex surgical anastomoses and unique pathology is necessary to inform radiologic interpretation. This book provides radiologists with the knowledge of the normal appearance of a transplanted organ, an understanding of imaging modalities that are best suited to answering clinical questions, an overview of the pathologies related to such organs and their appearance on various modalities, vascular and nonvascular complications, and techniques related to image-guided transplant interventions. .